The importance of nutrition in the treatment of Gestational Diabetes Mellitus: an integrative review (Research, Society and Development, 2022)
Gestational Diabetes Mellitus (GDM) is defined as a metabolic dosage group characterized by hyperglycemia, resulting from defects in insulin secretion, insulin action, or both, with any degree of glucose intolerance with onset or detection during pregnancy. The present research discussed the importance of nutrition in the treatment of patients with Gestational Diabetes Mellitus with the general objective of describing from the bibliographic analysis, the relevance of the Nutrition professional in the treatment of pregnant women who have gestational diabetes mellitus. The research was carried out in the form of an integrative review, the bibliographic method of a qualitative nature was adopted, and a literature review was carried out. The following descriptors in Portuguese were used: Nutrition. Pregnant. Diabetes. Gestational Diabetes Mellitus, between the years 2010 to 2022. The research results show that nutritional intervention is an important ally for the control of Gestational Diabetes Mellitus, leading to several benefits to maternal and fetal health.